Decolonizing science in Latin American art - Page, Joanna, 1974- (Modern Americas., 2021)
Decolonizing Science in Latin American Art explores art-science projects by Latin American artists, ranging from big-budget collaborations with NASA and MIT to homegrown experiments in artists' kitchens.